Managing the Resource Allocation Process: A Study of Corporate Planning and Investment. - Quirin, G. David; Bower, Joseph L. (Journal of Finance, 1971)
This is the definitive examination of strategic investment from the viewpoint of the people who run the company - the CEO and principal officers. It includes four case histories that follow specific investment projects from their inception to their approval by top management. It is A Harvard Business School Classics Edition.